MEMBANGUNKAN BAHASA YANG SEDANG TIDUR DI ALOR: REVITALISASI BAHASA ADANG (Awaken Sleeping Language: Revitalization of Adang Language in Alor) - Yulianti, Santy; Handayani, Retno; Ferdinandus, Pangkul (Jurnal Lingko : Jurnal Kebahasaan dan Kesastraan, 2021)
Revitalization locations for the Adang language learning process are carried out in Alaang Village. The choice of this village due to Alaang Village is located around 30 kilometers from the center of Kalabahi city and is in the middle of the Adang language speaker area. Although it is quite far from the city center, the Alaang people only use the Adang language among the older generation. The target of this activity is the young generation as the next generation of the Adang language. One revitalization activity deals with at least 20 teenagers or children. The learning process is focused on storytelling, poetry, poetry, and singing in Adang. The material is developed based on the daily life of the Adang tribe. The recommendation that can be proposed from this activity is the maintenance of the Adang language that can be carried out by inserting local language learning through local content in schools located in the Adang language area.